CARACTERÍSTICAS FÍSICAS DEL RESERVORIO EN EL CAMPO GEOTÉRMICO LAS PAILAS ESTIMADAS CON BASE EN DATOS SISMOLÓGICOS, ESTRUCTURALES Y RELACIONES DE POISSON (σ) - Taylor, Waldo (2011)
During the second half of 2002, a seismic swarm (more than 250 microearthquakes)was recorded at Las Pailas Geothermal Field (PGF) with local magnitude ML< 2.0 and depths bet-ween 1.0 and 5.5 km. 116 earthquakes were located and 86 were used to draw Poisson ratio (σ) maps.Using seismic distribution, structural data, polarization of the fastest S wave and field observations,I determined, identified and verified faults and fractures with NW and NE directions, where two ofthem are strike slip active faults. Based on Poisson ratios, data field and seismicity analysis, I conclude that PGF is a high-pressure water domain reservoir controlled by fault systems and can be divided in sectors according to three different conditions or classifications. The first condition has low σvalues (higher vapor amount) and low permeability, is located to the east and west limits of PGF,where the PGP-02 and PGP-05 wells are located. The second condition has high σ values (between0.24 and 0.30) normally suggesting higher fluids amount, within this sector wells PGP-04 and PGP-06 are located. The third sector has intermediate or higher σ values (0.18-0.23) and can be relatedwith phase shift areas along fault systems and where wells PGP-01 and PGP-03 are located.